2007
DOI: 10.1002/art.22880
|View full text |Cite
|
Sign up to set email alerts
|

Systemic autoimmune disease mortality and occupational exposures

Abstract: Objective. To generate hypotheses regarding occupational exposures that may cause systemic autoimmune diseases.Methods. Based on examination of US death certificates, we identified deaths in 26 states for which a cause was listed as rheumatoid arthritis (RA) (n ‫؍‬ 36,178), systemic lupus erythematosus (SLE) (n ‫؍‬ 7,241), systemic sclerosis (n ‫؍‬ 5,642), or other systemic autoimmune disease (n ‫؍‬ 4,270). Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated to estimate associations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 39 publications
6
93
2
2
Order By: Relevance
“…Exposure categories were established in routine registries (Brown et al 1997; Brown et al (1997), Sweden Cohort (1965-19831977-1989; nationwide registry-based cohorts of patients hospitalized for silicosis Diagnoses of silicosis as proxy for silica exposure 37 11.9-86.3 Mehlhorn et al (1999), Germany Cohort; incidence 243,900 highly exposed and 50,000 low-exposed male uranium miners Assessment of level of exposure in uranium miners 7.41 6.14-8.93 Rosenman et al (1999), USA Cohort (1987, individuals with silicosis from state registry system Mehlhorn et al 1999;Ziegler et al 1997) or using job titles (Rodnan et al 1967;Walsh 1999;Calvert et al 2003;Gold et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure categories were established in routine registries (Brown et al 1997; Brown et al (1997), Sweden Cohort (1965-19831977-1989; nationwide registry-based cohorts of patients hospitalized for silicosis Diagnoses of silicosis as proxy for silica exposure 37 11.9-86.3 Mehlhorn et al (1999), Germany Cohort; incidence 243,900 highly exposed and 50,000 low-exposed male uranium miners Assessment of level of exposure in uranium miners 7.41 6.14-8.93 Rosenman et al (1999), USA Cohort (1987, individuals with silicosis from state registry system Mehlhorn et al 1999;Ziegler et al 1997) or using job titles (Rodnan et al 1967;Walsh 1999;Calvert et al 2003;Gold et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a study of 52,277 cases and 260,632 controls obtained from death certificates identified that mortality risk from autoimmune diseases, specifically rheumatoid arthritis (OR=1.3, 95% CI: 1.1-1.5) and SLE (OR=1.2, 95% CI: 1.0-1.4), is increased in patients previously exposed to mining as determined by the occupational code "mining machine operator" on the subject's death certificate. 34,35 Most recently, a Swedish population-based case-control study of 2288 WG patients diagnosed by ICD#9 hospital discharge code and gender-, age-, regionmatched controls (10 per case) identified borderline risk (OR=1.6, 95% CI: 0.8-3.1) for miners after a validation step excluded cases not fulfilling ACR criteria. 36 We observed a positive association of exposure to rodenticides and a weakly positive association of exposure to insecticides with the development of WG.…”
Section: Discussionmentioning
confidence: 99%
“…Noonan et al [39] have, in fact, found that workers in an asbestos-contaminated vermiculite mining company were at twice the risk of either rheumatoid arthritis, systemic lupus erythematosus, or SSc compared with the unexposed population. Nevertheless, in this group of exposed patients, because asbestos was concurrent with crystalline silica exposure (contaminated vermiculite), it is difficult to assess the role of each material separately.…”
Section: Asbestosmentioning
confidence: 99%